2019
DOI: 10.1155/2019/5975837
|View full text |Cite
|
Sign up to set email alerts
|

Value of Time to Positivity of Blood Culture in Children with Bloodstream Infections

Abstract: Objective This study was to investigate the microbiological characteristics and the relationship between the time to positivity (TTP) of blood cultures and different bacterial species and to assess the clinical value of TTP in children with bloodstream infections (BSIs). Methods The TTP of all the blood cultures from children with suspected BSIs was retrospectively collected in 2016. The microbiological characteristics and the relationship between the TTP of blood cultures and different bacterial species were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
4
15
0
Order By: Relevance
“…Up to now, many studies in the literature have reported that TTP has a certain predictive value for the clinical significance of CoNS in blood culture, 2,3,8 which is also confirmed by the results of this current study by our group. Zhang Yu et al studied 160 children and found that the optimal critical value for TTP that could be used to determine a child's blood flow infection and contamination was 17.35 hours.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Up to now, many studies in the literature have reported that TTP has a certain predictive value for the clinical significance of CoNS in blood culture, 2,3,8 which is also confirmed by the results of this current study by our group. Zhang Yu et al studied 160 children and found that the optimal critical value for TTP that could be used to determine a child's blood flow infection and contamination was 17.35 hours.…”
Section: Discussionsupporting
confidence: 90%
“…Studies from Ireland showed that the TTP of all pathogens of bloodstream infections was <24 hours 8 . A more recent study by Pan et al, gave a TTP of 22.72 hours 2 . American Pardo believed that there was almost no real blood stream infection detected after 48 hours of culture, so it was recommended that antibiotic use should be downgraded after 48 hours, which was also verified in the study of Abdelhamid 6,9 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Physical signs and symptoms, though useful in identifying possible cases, have limited specificity in diagnosis. 6,7 Growing resistance to conventional and even newer antibiotics is also a matter of serious concern. 17 Blood culture plays an important role by timely and correctly identifying the underlying pathogens and based on their drug resistance patterns guide the clinicians regarding the empirical as well as the definitive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…4 Blood culture remains the gold standard for laboratory diagnosis of bloodstream infections (BSIs) in infants and children. 5,6 Although both Gram negative and Gram positive bacteria are associated with these infections, Gram negative bacterial infections are more fatal and cause more serious therapeutic problems as multi drug resistant strains are more common among them. [7][8][9] In almost all cases, empiric antimicrobial therapy is initiated before the results of blood culture are available.…”
Section: Introductionmentioning
confidence: 99%